Latest trend ectopic pregnancy management in a tertiary health center: a retrospective cohort study - Yıldız Akdaş Reis; Merve Özkan; Seval Yılmaz Ergani; Müjde Can İbanoğlu; Doğukan Özkan; Tuğba Kınay; Salim Erkaya (Perinatal Medicine Foundation, 2022)
Objective: The aim of this study is to investigate the incidence, risk factors, clinical presentation, management, morbidity and mortality of ectopic pregnancy (EP) by evaluating all cases treated in a tertiary care center in Ankara. Methods: A total of 1243 cases were retrospectively studied who were diagnosed with ectopic pregnancy during the clinical course and were treated in the early pregnancy unit between January 2014 and December 2018. Demographic information from hospital records, e.g., risk factors, ultrasound findings, initial and followed up b-hCG levels, and treatment methods (followed up, medical, and surgical) were recorded. Results: The incidence of EP was 7 per 1000 pregnancies. The mean age was 30.64±5.71 years. The most common risk factors for EP were previous abdominal surgery (37.8%) and previous miscarriage (28.6%). Eighty-three (22%) of patients diagnosed between 2013 and 2014, 129 (34.2%) of patients diagnosed between 2015 and 2016, and 165 (43.8%) of patients diagnosed between 2017 and 2018 had a history of Cesarean section. Seventy-seven (6.2%) cases were followed up, 487 (39.2%) were treated surgically, and 772 (62.1%) were treated with methotrexate. Conclusion: Delivery by Cesarean section is a risk factor for the development of EP. Cesarean section has been shown to be an important factor in the increase of the incidence of EP over the years. As a result of this increase, new treatments have been developed and conservative surgical or drug treatments have been initiated. Close monitoring of the current literature evaluating ectopic pregnancies and treatment according to this literature will decrease mortality and morbidity rates.